American Slavery, Irish Freedom : Abolition, Immigrant Citizenship, and the Transatlantic Movement for Irish Repeal - Murphy, Angela F., 1967- (Book collections on Project MUSE., 2010)
In American Slavery, Irish Freedom, Angela F. Murphy examines the interactions among abolitionists, Irish nationalists, and American citizens as the issues of slavery and abolition complicated the first transatlantic movement for Irish independence. For Irish Americans, the call of Old World loyalties, perceived duties of American citizenship, and regional devotions collided as the slavery issue intertwined with their efforts on behalf of their homeland. By looking at the makeup and rhetoric of the American repeal associations, the pressures on Irish Americans applied by both abolitionists and.